Formulation of guidelines to resolve medical emergencies in dental practice: An overview - Farouk M Sakr; Kais G Al-Obaidy; Lokesh J Shetty; Fathy A Behery; Mansour K Assery; Abdel Nasser I Adam; Mohamed J Patel (Wolters Kluwer Medknow Publications, 2016)
Dentists are prone to face unpredictable medical emergency crises in their patients during dental practice. These seldom but usually occurring events require diagnosis for safe and effective management. Therefore, dental care professionals are required to be equipped with information and training on how to manage medical emergencies (MEs) including drug administration. An outline of what essential basic life support equipment and medications require in dental clinics to manage MEs are provided with recommendation for training to handle those medical events. Effective and safe dental practice require to providing graduate and undergraduate dentistry students with updated information and training on medical emergencies and how to handle different equipment and drugs associated with such events.